2011
DOI: 10.1021/jf200259n
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Geraniol 10-Hydroxylase Reveals Its Dual Function in the Biosynthesis of Terpenoid and Phenylpropanoid

Abstract: Geraniol 10-hydroxylase (G10H), a cytochrome P450 monooxygenase, has been reported to be involved in the biosynthesis of terpenoid indole alkaloids. The gene for Catharanthus roseus G10H (CrG10H) was cloned and heterologously expressed in baculovirus-infected insect cells. A number of substrates were subjected to assay the enzyme activity of CrG10H. As reported in a previous study, CrG10H hydroxylated the monoterpenoid geraniol at the C-10 position to generate 10-hydroxygeraniol. Interestingly, CrG10H also cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
(49 reference statements)
2
28
0
Order By: Relevance
“…Its peak eluted at the retention time of 15.2 min appeared to have a pattern of mass fragmentation (m/z 67, 81, 109, 121 and 152, Fig. 6B) that was very similar to the reported mass fragmentation of 8-OH geraniol (2) (Collu et al, 2001;Sung et al, 2011). However, attempts to purify both CYP76F45 and CsCPR I from the 20,000 g microsomal fractions for kinetic studies were not successful due to the loss of enzyme activity in the process.…”
Section: Functional Identification Of Cyp76f45 and Cscpr Isupporting
confidence: 76%
See 2 more Smart Citations
“…Its peak eluted at the retention time of 15.2 min appeared to have a pattern of mass fragmentation (m/z 67, 81, 109, 121 and 152, Fig. 6B) that was very similar to the reported mass fragmentation of 8-OH geraniol (2) (Collu et al, 2001;Sung et al, 2011). However, attempts to purify both CYP76F45 and CsCPR I from the 20,000 g microsomal fractions for kinetic studies were not successful due to the loss of enzyme activity in the process.…”
Section: Functional Identification Of Cyp76f45 and Cscpr Isupporting
confidence: 76%
“…G8H has been suggested to be a potential site for regulation of the production of secologanin, which is involved in the biosynthesis of monoterpenoid indole alkaloids and iridoid monoterpenoids (Hofer et al, 2013). The enzyme from Catharanthus roseus has also been shown to catalyze the 3 0 hydroxylation of naringenin to produce eriodictyol in the flavonoid biosynthetic pathway (Sung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the experimental study, it was found that the catalytic activity of CrG10H was approximately 10 times more effi cient with geraniol than with naringenin. (64) In another study, the activity of key enzymes of ammonium assimilation in cell-free extracts of soybean rhizobia characterized with different effectiveness in symbiosis was investigated. The nonspecific flavonoid naringenin has not stimulated glutamine synthetase (GS)-activity of the highly effi cient rhizobia, but has stimulated the activity of glutamate dehydrogenase.…”
Section: Effect Of Naringenin On Cardiovascular Systemmentioning
confidence: 99%
“…To analyze the substrate specificity of CYP71D351 and CYP71D12, microsomes from yeast strains expressing each enzyme were assayed against several different compounds, including MIAs, MIA precursors, and naringenin, which is a hydroxylatable flavonoid with aromatic ring, accumulated in leaf epidermis and substrate of geraniol 10-hydroxylase (Sung et al, 2011). LC-MS analysis of reaction mixtures revealed that, among all the tested compounds, only tabersonine (Aspidospermatype MIA) and to a lesser extent the two closely related compounds, 2,3-dihydro-3-hydroxytabersonine and 2,3-dihydrotabersonine, were metabolized by the two enzymes (Table I).…”
Section: Substrate Specificity Analysismentioning
confidence: 99%